+0  
 
0
164
6
avatar+194 

\(\int_{3}^{4} (x^2-1)*e^x/e-7ex+11e dx=?\)

Whitespy001  Jun 2, 2017
edited by Whitespy001  Jun 2, 2017
Sort: 

6+0 Answers

 #1
avatar
+1

Compute the definite integral:
 integral_3^4 (e^(x - 1) (x^2 - 1) - 7 e x + 11 e) dx


Integrate the sum term by term and factor out constants:
 = integral_3^4 e^(x - 1) (x^2 - 1) dx + -7 e integral_3^4 x dx + 11 e integral_3^4 1 dx


Expanding the integrand e^(x - 1) (x^2 - 1) gives e^(x - 1) x^2 - e^(x - 1):
 = integral_3^4 (e^(x - 1) x^2 - e^(x - 1)) dx + -7 e integral_3^4 x dx + 11 e integral_3^4 1 dx


Integrate the sum term by term and factor out constants:
 = integral_3^4 e^(x - 1) x^2 dx - integral_3^4 e^(x - 1) dx + -7 e integral_3^4 x dx + 11 e

 

integral_3^4 1 dx
For the integrand e^(x - 1) x^2, substitute u = x - 1 and du = dx.
This gives a new lower bound u = 3 - 1 = 2 and upper bound u = 4 - 1 = 3:
 = integral_2^3 e^u (u + 1)^2 du - integral_3^4 e^(x - 1) dx + -7 e integral_3^4 x dx + 11 e

 

integral_3^4 1 dx
Expanding the integrand e^u (u + 1)^2 gives e^u u^2 + 2 e^u u + e^u:
 = integral_2^3 (e^u u^2 + 2 e^u u + e^u) du - integral_3^4 e^(x - 1) dx + -7 e integral_3^4 x dx + 11 e integral_3^4 1 dx


Integrate the sum term by term and factor out constants:
 = integral_2^3 e^u u^2 du + 2 integral_2^3 e^u u du + integral_2^3 e^u du - integral_3^4 e^(x - 1) dx + -7 e integral_3^4 x dx + 11 e integral_3^4 1 dx


For the integrand e^u u^2, integrate by parts, integral f dg = f g - integral g df, where 
 f = u^2, dg = e^u du, df = 2 u du, g = e^u:
 = e^u u^2 right bracketing bar _2^3 + integral_2^3 e^u du - integral_3^4 e^(x - 1) dx + -7 e integral_3^4 x dx + 11 e integral_3^4 1 dx


Evaluate the antiderivative at the limits and subtract.
 e^u u^2 right bracketing bar _2^3 = e^3 3^2 - e^2 2^2 = e^2 (9 e - 4):
 = e^2 (9 e - 4) + integral_2^3 e^u du - integral_3^4 e^(x - 1) dx + -7 e integral_3^4 x dx + 11 e integral_3^4 1 dx


Apply the fundamental theorem of calculus.
The antiderivative of e^u is e^u:
 = e^2 (9 e - 4) + e^u right bracketing bar _2^3 - integral_3^4 e^(x - 1) dx + -7 e integral_3^4 x dx + 11 e integral_3^4 1 dx


Evaluate the antiderivative at the limits and subtract.
 e^u right bracketing bar _2^3 = e^3 - e^2 = (e - 1) e^2:
 = (e - 1) e^2 + e^2 (9 e - 4) - integral_3^4 e^(x - 1) dx + -7 e integral_3^4 x dx + 11 e integral_3^4 1 dx


Apply the fundamental theorem of calculus.
The antiderivative of e^(x - 1) is e^(x - 1):
 = (e - 1) e^2 + e^2 (9 e - 4) + (-e^(x - 1)) right bracketing bar _3^4 + -7 e integral_3^4 x dx + 11 e integral_3^4 1 dx


Evaluate the antiderivative at the limits and subtract.
 (-e^(x - 1)) right bracketing bar _3^4 = (-e^(4 - 1)) - (-e^(3 - 1)) = -(e - 1) e^2:
 = e^2 (9 e - 4) + -7 e integral_3^4 x dx + 11 e integral_3^4 1 dx


Apply the fundamental theorem of calculus.
The antiderivative of x is x^2/2:
 = e^2 (9 e - 4) + (-(7 e x^2)/2) right bracketing bar _3^4 + 11 e integral_3^4 1 dx


Evaluate the antiderivative at the limits and subtract.
 (-(7 e x^2)/2) right bracketing bar _3^4 = (-(7 e 4^2)/2) - (-(7 e 3^2)/2) = -(49 e)/2:
 = -(49 e)/2 + e^2 (9 e - 4) + 11 e integral_3^4 1 dx


Apply the fundamental theorem of calculus.
The antiderivative of 1 is x:
 = -(49 e)/2 + e^2 (9 e - 4) + 11 e x right bracketing bar _3^4


Evaluate the antiderivative at the limits and subtract.
 11 e x right bracketing bar _3^4 = 11 e 4 - 11 e 3 = 11 e:
 = e^2 (9 e - 4) - (27 e)/2
Which is equal to:
Answer: | = 1/2 e (-27 - 8 e + 18 e^2)

Guest Jun 2, 2017
 #2
avatar+194 
0

Thank you i find the same too but the result say its :

10e^3 - 5e^2 -49e/2 + 11e and i cant find it but is not false because it the result from ministry ... I dont know...Thank you after all!!!

Whitespy001  Jun 2, 2017
 #3
avatar
+1

Just make sure that the Integral is bracketed accurately. Example: (e^x/e) - 7ex +11e dx? Or is it:

e^x/(e - 7ex + 11e) dx?

Guest Jun 2, 2017
 #4
avatar+194 
+1

no its e^(x-1) and i write it e^x/e coz i cant write it there like this

Whitespy001  Jun 2, 2017
 #5
avatar+26242 
+1

The result you quote isn't consistent with the integral you specify:

 

\(\int_3^4(x^2-1)e^{x-1}-7ex+11edx=9e^3-4e^2-\frac{27e}{2}\)

 

However:

 

\(\int_3^4x^2e^{x-1}-7ex+11edx=10e^3-5e^2-\frac{27e}{2}\)

 

Note that  -49e/2 + 11e  =  -27e/2

.

Alan  Jun 2, 2017
edited by Alan  Jun 2, 2017
 #6
avatar+194 
+1

Yes thank you i know i find it but becaise the result is 

10e^3 - 5e^2 -49e/2 + 11e from ministry i think i was false but im not .Thank you!

Whitespy001  Jun 2, 2017

8 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details